Efficient Rapid Microwave-Assisted Route to Synthesize Monodispersive Pt Nanoparticles and Their Electrocatalytic Activity for Methanol Oxidation. (4th May 2014) - Wang, Libin; Xu, Wenjun; Wu, Xiao; Li, Qian; Wang, Zhiming; Zheng, Xiuwen
Abstract : High monodispersive Pt nanoparticles (NPs) have been prepared via two facile and environmentally-friendly procedures, either through a traditional solvothermal route (T-Pt NPs) or via a microwave-assisted route (M-Pt NPs). The transmission electron microscopy (TEM) shows the high Monodispersity for T-Pt NPs with the average diameter being ca.2.79 nm and the pod-like nanostructure for M-Pt NPs, which indicate the efficiency of both methods. An optimal choice of protocol allows reducing the reaction time from 2 hours (T-Pt NPs) to 20 minutes (M-Pt NPs). The electrocatalytic activities of as-prepared Pt NPs were investigated by cyclic voltammetry, showing very high catalytic activity for a methanol oxidation reaction.